The Effectiveness of the Flipped Classroom Learning Model on Students' Critical Thinking Skills in Civics Subjects - Erma Mawaryanto; Anindita Trinura Novitasari; Bagus Imam Faisal (FKIP Universitas Halu Oleo, 2024)
It is not enough for learners to be knowledgeable, but they must also have critical thinking skills. The problem in the research comes from the lack of critical thinking skills of class VIII-A students in Civics subjects at UPTD SMP Negeri 1 Kamal. Students tend to be passive, lack of understanding of the material, lack of courage in expressing opinions or questions about the subject matter taught. This problem requires a flipped classroom learning model that aims to test the effectiveness of the learning model on students' critical thinking. This type of research uses exploratory with a quantitative approach. The data analysis shows that the application of the flipped classroom model has a positive effect on students' critical thinking skills. The results of hypothesis testing in this study also resulted in H1 being accepted and obtained a value of 6.265> 2.042, so the t-count > t-table hypothesis formulated in this study is accepted, which means that the flipped classroom learning model is effective on students' critical thinking skills. The results in this study show the effectiveness of this learning model is supported by the flipped classroom learning model in Civics subjects can create learning in the classroom more actively and can encourage students to think critically optimally. In addition, it helps teachers in learning in the classroom more effectively so that it facilitates the process of evaluating learning on students' critical thinking skills and learning outcomes.